Leaching ION Paduan Logam ZN-1MG Dalam Larutan Simulated Body Fluids (SBF) - Suci Puspita Anggraini (Jurnal Indonesia Sosial Teknologi, 2022)
Biomaterials are natural or synthetic materials that interact directly with the tissues and fluids of an organism's biological systems. One of these biomaterials is Zn-1 Mg alloy which is potentially biodegradable. This study aims to contribute to the study of As-rolled variation of Zn-1Mg alloy leaching using quantitative methods which were carried out experimentally. To ensure the presence of leaching ions from the Zn-1Mg alloy, an immersion test was carried out using simulated body fluids as electrolyte solutions by the criteria set out in ASTM F160, F3268 as a substitute for body fluids. The results obtained that the Zn and Mg ions in the ZN-1Mg alloy underwent leaching, where the highest leaching of Zn ions was on day 3 at 0.743 ppm but for Mg ions on day 21 more leached as much as 0.354 ppm compared to ion concentrations on other days.